Integration of environmental, social and governance (ESG) into the supply chain of ammonia: Case study of Africa - Nam Nghiep Tran; Lucy Kate Penna; Isla May Heath; Muhammad Yousaf Arshad; Marc Escribà Gelonch; Jose Luis Osorio Tejada; Mohammad Mohsen Sarafraz; John Suberu; Martin Fregene; Bernard Rolfe; Volker Hessel (Sustainable Futures, 2025)
Ammonia is a cornerstone of global agricultural productivity, yet its traditional production and distribution systems remain highly centralised, carbon-intensive, and often inaccessible in under-resourced regions. An integration of ESG factors into a decentralised ammonia supply chain model, using Africa as a case study to highlight broader global relevance and overcoming a research gap in financial engineering and business strategies. The research investigates the feasibility of deploying small-scale, locally distributed production facilities as an alternative to conventional large-scale models, particularly in regions facing high transport costs and limited infrastructure. Innovative, low-emission technologies, such as high thermal plasma, mini-Haber-Bosch systems and others are evaluated for their techno-economic potential, including the application of environmental credits and future carbon tax scenarios. A comprehensive supply chain simulation demonstrates that decentralised ammonia production can achieve competitive costs of USD 232 per tonne when ESG-aligned strategies are applied. Beyond cost-efficiency, the study offers a strategic framework to operationalise ESG integration in global fertiliser supply chains, with implications for climate resilience, local economic development, and long-term food security in emerging markets.